1971
DOI: 10.2134/agronj1971.00021962006300010005x
|View full text |Cite
|
Sign up to set email alerts
|

Row Spacing and Population Effects on Corn Yields1

Abstract: During a 3‐year period at three locations, the effects of populations and row spacings on 10 corn (Zea mays L.) hybrids (early, medium, and late maturing) were evaluated. Grain yields were increased as the width between rows decreased. Yields were usually higher with the late maturing variety planted at a medium or high population. Some exceptions to this generalization were observed. Percentage moisture in the grain at harvest was not affected by row spacings or plant populations but was affected by the hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 4 publications
1
22
0
1
Order By: Relevance
“…However, mechanical cultivation for weed control and post-emergence herbicide treatments are more difficult in narrow row cultivation. Studies conducted in the USA and Canada indicated that the grain yield increases with narrower rows have been relatively small and quite variable (Lutz et al 1971, Nielsen 1988, Farnham 2001. Responses to narrowing row spacing have been also varied and inconsistent in silage corn (Bryant and Blaser 1968).…”
Section: Introductionmentioning
confidence: 99%
“…However, mechanical cultivation for weed control and post-emergence herbicide treatments are more difficult in narrow row cultivation. Studies conducted in the USA and Canada indicated that the grain yield increases with narrower rows have been relatively small and quite variable (Lutz et al 1971, Nielsen 1988, Farnham 2001. Responses to narrowing row spacing have been also varied and inconsistent in silage corn (Bryant and Blaser 1968).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the general tolerance to a great range of environmental stresses (Tollenaar 1991) and improved light interception architecture of recently developed hybrids (Girardin and Tolenaar 1994) could potentially allow for greater yields under high population densities than were achievable with older hybrids. For a given planting density, a 5 to 10% improvement in maize yields has been reported under narrow (0.38 m) vs. standard rows (0.76 m) (Hoff and Mederski 1960;Stickler 1964;Yao and Shaw 1964;Brown et al 1970;Hunter et al 1970;Lutz et al 1971;Stivers et al 1971;Stanley and Rhoads 1975;Camp et al 1985;Karlen and Camp 1985). An earlier study by Stivers et al (1971) demonstrated that there were more barren ears, contributing to lower yield, in wider rows (102, 76 cm) than in narrow rows (0.51 m) under drought stress conditions.…”
mentioning
confidence: 99%
“…They also observed a reduction in the weight per kernel when stand density was increased. An increase in ear weight per plant with a decrease in plant population and with increased time required for maturity has been observed (Lutz et al, 1971). …”
Section: Kernel Weightmentioning
confidence: 97%
“…They reported that the relative proportions of the different plant parts varied between an early and a late hybrid, but were affected only slightly by differences in plant population. Lutz et al (1971) in a three-year experiment studied ten different maturing hybrids and found that the ear to stover ratio varied from 2.20:1 to 0.88:1 depending on the hybrid. The ratio was unaffected by row spacing or plant population.…”
Section: Dry Matter Production and Its Partitionmentioning
confidence: 99%